2011
DOI: 10.5301/ejo.5000017
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound biomicroscopy findings in fireworks-related blunt eye injuries

Abstract: Our study showed the value of UBM in the assessment of severely contused eyes and hyphema. It made possible evaluation for dialyses and recessions at presentation. Ultrasound biomicroscopy illustrated diverse subclinical disruptions in clinically invisible anterior segment structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…reported that UBM detected 94.4% of the OFBs evaluated, while B‐scans and CT detected 36.5% and 88.9%, respectively 13 . Since then, UBM has been reported to be an effective technique in detecting OFBs and characterizing their composition 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that UBM detected 94.4% of the OFBs evaluated, while B‐scans and CT detected 36.5% and 88.9%, respectively 13 . Since then, UBM has been reported to be an effective technique in detecting OFBs and characterizing their composition 24 …”
Section: Discussionmentioning
confidence: 99%
“…13 Since then, UBM has been reported to be an effective technique in detecting OFBs and characterizing their composition. 24 CT is the most widely used method for detecting and localizing foreign bodies 25 and was historically considered the most sensitive imaging technique for OFBs. CT creates images by detecting changes in the intensity of X-rays as they penetrate objects.…”
Section: B-scan (Nmentioning
confidence: 99%
“…UBM was effective in identifying iridodialysis, cyclodialysis, angle recession, lens subluxation, and anterior segment foreign body in these patients. Many of these findings were not identified on clinical examination, and were only found upon UBM imaging, illustrating the value of UBM as an essential tool in the assessment of subclinical injury to the anterior segment, particularly in the setting of explosive or ballistic injury mechanism [51]. Another study evaluated 53 eyes of patients who had fireworks related injuries in Southern China.…”
Section: Ocular Traumamentioning
confidence: 99%
“…B-scan imaging and ultrasound biomicroscopy (UBM) can also assist in characterizing anterior and posterior segment pathology in the setting of ocular trauma. UBM can elicit additional findings such as cyclodialysis or angle recession [ 14 , 15 ]. B-scan ultrasonography can provide information regarding potential globe rupture, IOFBs, lens dislocation, vitreous hemorrhage, membranes, retinal tears, and retinal or choroidal detachments [ 16 ].…”
Section: Introductionmentioning
confidence: 99%